2018
DOI: 10.1111/mila.12194
|View full text |Cite
|
Sign up to set email alerts
|

Implicit bias, ideological bias, and epistemic risks in philosophy

Abstract: It has been argued that implicit biases are operative in philosophy and lead to significant epistemic costs in the field. Philosophers working on this issue have focused mainly on implicit gender and race biases. They have overlooked ideological bias, which targets political orientations. Psychologists have found ideological bias in their field and have argued that it has negative epistemic effects on scientific research. I relate this debate to the field of philosophy and argue that if, as some studies sugges… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 85 publications
(153 reference statements)
0
9
0
Order By: Relevance
“…In contrast, the arguments typically advanced for counteracting a lack of diversity in academia focus primarily on research in academia (e.g., enhanced social criticism, avoidance of research lacunas, etc., Longino 2002;Intemann 2011;Duarte et al 2015). I agree and have argued myself (Peters 2019;Peters et al 2020, p. 536) that there are good reasons to tackle a lack of political diversity when it comes to research environments in academia. When it comes to education, however, the argument captured in (P1)-(C4) suggests that a lack of diversity might produce significant ethical and epistemic benefits that point in the opposite direction.…”
Section: Objectionsmentioning
confidence: 93%
See 2 more Smart Citations
“…In contrast, the arguments typically advanced for counteracting a lack of diversity in academia focus primarily on research in academia (e.g., enhanced social criticism, avoidance of research lacunas, etc., Longino 2002;Intemann 2011;Duarte et al 2015). I agree and have argued myself (Peters 2019;Peters et al 2020, p. 536) that there are good reasons to tackle a lack of political diversity when it comes to research environments in academia. When it comes to education, however, the argument captured in (P1)-(C4) suggests that a lack of diversity might produce significant ethical and epistemic benefits that point in the opposite direction.…”
Section: Objectionsmentioning
confidence: 93%
“…(Richard Buckminster Fuller) 1 Many studies have shown that people frequently engage in politically motivated cognition: we often tend to conform our assessments and beliefs about information to our political goals and political identity rather than to accuracy (Kunda 1990;Taber and Lodge 2006;Nisbet et al 2015;Kahan 2016). Politically motivated cognition, which is taken to be less than fully epistemically rational because it involves a diminished sensitivity to facts (Huemer 2016;Ringel et al 2019), has recently become a hot topic in philosophy (Gerken 2019;Peters 2019;Talisse 2019;Carter and McKenna 2020). The present paper offers a social epistemological investigation of a specific type of politically motivated cognition.…”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation
“…Focusing on task-relevant informational differences, many philosophers of science hold that it is precisely because DD and CD are commonly connected that DD can be epistemically beneficial: via adding cognitive differences to a group, DD can enhance social criticism, help counteract biased belief formation, increase creativity, facilitate a thorough exploration of problem space, and reduce research lacunas (Longino 2002 : 132f; Solomon 2009 ; Fehr 2011 ; Rolin 2017 : 118f; Peters 2019 ). That is, many philosophers take the epistemic gains tied to DD to be mediated by the corresponding CD (Steel et al 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, confirmation bias (or 'myside bias'), 1 that is, people's tendency to search for information that supports their beliefs and ignore or distort data contradicting them (Nickerson 1998;Myers and DeWall 2015: 357), has frequently been discussed in the media, the sciences, and philosophy. The bias has, for example, been mentioned in debates on the spread of "fake news" (Stibel 2018), on the "replication crisis" in the sciences (Ball 2017;Lilienfeld 2017), the impact of cognitive diversity in philosophy (Peters 2019a;Peters et al forthcoming;Draper and Nichols 2013;De Cruz and De Smedt 2016), the role of values in inquiry (Steel 2018;Peters 2018), and the evolution of human reasoning (Norman 2016;Mercier and Sperber 2017;Sterelny 2018;Dutilh Novaes 2018).…”
mentioning
confidence: 99%